Sleep Quality in Chilean Professional Soccer Players - Jorquera Aguilera, Carlos.; Barahona Fuentes, Guillermo Daniel.; Pérez Peña, María José.; Yeomans Cabrera, María Mercedes.; Huerta Ojeda, Álvaro Cristian. (MDPI, 2021)
Recent research has shown that good sleep quality has a positive effect on physical performance. However, sleep quality in Chilean professional soccer players is unknown. The purpose of this study was to determine sleep quality in Chilean professional soccer players. It was a cross-sectional, explanatory study with observable variables. The sample consisted of 94 Chilean male soccer players belonging to four professional clubs. The main variable was the Sleep Quality Index, evaluated through the Pittsburgh questionnaire (Spanish version). After estimating sleep quality individually, the four professional soccer clubs' comparison was performed through a one-factor ANOVA. The Pearson test was used to relate the questionnaire variables; the significance level was p < 0.05. In the global analysis of the Pittsburgh Sleep Quality Index, a value of 4.75 ± 2.29 on a scale of 0-21 was observed, with no significant differences between the clubs evaluated (p > 0.05). Based on the results obtained, Chilean male professional soccer players present good sleep quality. However, the high values of "sleep latency" and "sleep disturbances" are indicators that should be worked on by the multidisciplinary team of each professional club. They should develop strategies to improve sleep hygiene, encourage good sleep, and fall asleep efficiently.
Keywords: Sleep quality index.; Physical performance.; Professional soccer players.